The Influence of Rapid Serial Visual Presentation on Performance in a Video Game. (September 2013) - Proaps, Alexandra B.; Bliss, James P.
The military has investigated the use of hand held devices and video games for training and mission planning. The purpose of this study was to continue previous research investigating the influence of rapid serial information presentation (RSVP) of intelligence reporting on task speed and reading comprehension. Fifty participants moved through a computer game to find a target as quickly as possible based on intelligence reports. There were two presentation styles (RSVP or traditional) and two intelligence formats (content words or full sentences). There were no between group differences in terms of search task performance within the game. Individuals scored higher on reading comprehension tests in the traditional text presentation group when shown content words and individuals in the traditional text presentation group when shown full sentences. We are conducting further analyses to address specific differences in performances and reading comprehension between groups. The results of this study suggest researchers and trainers should continue to investigate rapid serial information presentation to determine if it can be employed during training for multiple types of tasks.